Ecology of sea ice biota. 1. Habitat, terminology, and methodology - Horner, Rita; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjorn; Hoshiai, Takao; Legendre, Louis; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
Polar regions are covered by extensive sea ice that is inhabited by a variety of plants and animals. The environments where the organisms live vary depending on the structure and age of the ice. Many terms have been used to describe the habitats and the organisms. We here characterize the habitats and communities and suggest some standard terms for them. We also suggest routine sampling methods and reporting units for measurements of biological and chemical variables.
Keywords: Sørishavet; biodiversitet; havis; marin biologi; polarområdene; økologi

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi